Kredibilitas Koran Pabelan Dimata Mahasiswa Universitas Muhammadiyah Surakarta - Andrianto, Karisma Rio, Dian Purworini, S. Sos. MM (2017)
Abstracts This study is to explores about credibility of newspaper. The credibility is that the Pabelan Newspaper in the eyes of the members Badan Eksekutfi Mahasiswa of the Universitas Muhammadiyah Surakarta. This research was conducted in the city of Surakarta at Universitas Muhammadiyah Surakarta. The quantitative descriptive methodology arranged to support the study while the measurement scale used Lingkert scale and using the questionnaire as a data source. The sample of this research is an active member of Badan Eksekutif Mahasiswa Universitas Muhammadiyah Surakarta. Credibility in the measure through three indicators, namely three factors expertise, trustworthiness, and attractiveness found that the credibility of the Pabelan Newspaper in the eyes of the Badan Ekskutif Mahasiswa of Universitas Muhammadiyah Surakarta is quite positive. In the outline of the Pabelan Newspaper is credible as the Campus Newspaper. But to do the evaluation again in some variable item because there are still weaknesses in some of the variables that can affect the crediblity Pabelan Newspaper decreased. This research while measurment Pabelan Newspaper in the eyes of Students where the credibility of research related to the Newspaper this is the first research for Pabelan Newspaper after 11 years of its existence that makes this study interesting and helpful.